Preparasi dan Karakteristik Floating Tablet Ekstrak Daun Jambu Biji (Psidium guajava L.) dengan Variasi Kombinasi Xanthan Gum dan HPMC: Preparation and Characteristics of Floating Tablets of Guava Leaf Extract (Psidium guajava L.) With Variations of Xanthan Gum and HPMC Combinations - Septia Andini; Siti Sa’diah; Suci Puspa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Floating drug delivery system (FRDDS) is a new drug delivery system that is intended to prolong the time of drugs in the stomach. One form of the gastroretentive system is a floating tablet, which can float and stay in the stomach for some time. Preparations with this system are suitable for use in drugs that have an action on the stomach. Gastritis is defined as an inflammation or swelling of the inner lining of the stomach. Guava leaves are proven to have active ingredients that can act as anti-ulcers. This study aims to formulate floating tablets and determine the optimal combination of HPMC with xanthan gum in the formulation of floating tablets of guava leaf extract based on flotation testing and in vitro dissolution profiles. The extract was made using maceration method with 96% ethanol as solvent. The tablets were made in a number of 3 formulas using the wet granulation method. Each tablet weighed 500 mg with a combination of various types of HPMC K100M, HPMC K15M, HPMC K4M with xanthan gum as a floating agent. The formula produced the best tablet quality with a combination of HPMC K100M and xanthan gum as a floating agent. Based on the results of the in vitro dissolution profile, the drug release rate ranged from 23,604% - 26,846% with in 360 minutes (6 hours).